THE NEED TO IMPROVE HUMAN’S NOOSPHERICAL RELATIONSHIP TO NATURE - Abdumalikov Abdulatif Abidjanovich (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2022)
This article examines the role and importance of the noosphere concept in the system of human-nature relations. Also, the tasks of increasing the rational attitude of man to nature and measures for its implementation are analyzed.